PEMBERDAYAAN MASYARAKAT TERHADAP LIMBAH TERNAK SAPI SEBAGAI BIOGAS DAN PUPUK ORGANIK DI DESA BUBE BARU KECAMATAN SUWAWA KABUPATEN BONE BOLANGO - Umbang Arif Rokhyati (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
So far cattle waste has not been fully utilized as biogas and organic fertilizer. Biogas is a gas produced by anaerobic activity or fermentation from organic materials, including cattle waste. Making biogas produces a new waste which is also called slurry or biogas dregs. This slurry is used as organic fertilizer that can be applied in agriculture and plantations. Organic Fertilizer is fertilizer derived from the remaining manure of livestock that has undergone a process of decomposition or weathering. The implementation method in this study uses a descriptive qualitative approach by displaying a detailed description of a situation and the data collected is in the form of words or pictures and not numbers. such as: Location Observation/Survey, Interview and Outreach. The results of this study are that some people already understand the process of making organic fertilizer but not with biogas and most still do not understand the process of making biogas or organic fertilizer and still need education in making biogas or organic fertilizer in order to create potential that will be very useful in the lives of rural communities. as well as improving the economy of the people of Bube Baru Village, Suwawa District, Bone Bolango Regency.